PELAKSANAAN MAKSIM KUALITAS DAN KUANTITAS DALAM IKLAN KOMERSIAL DI TELEVISI (KAJIAN ANALISIS PERCAKAPAN) - Redo Andi Marta (Program Studi Pendidikan Bahasa Indonesia, , Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mahaputra Muhammad Yamin, 2020)
This study aims to explain the implementation of the maxim of quality and quantity in a conversation. Conversation can be done under any circumstances. In this study the conversations were scrutinized conversations in a commercial commercial on television. This type of research is a research based on qualitative approach using descriptive method. Source of date used speech-speech in the form of conversations that exist in commercial commercials on television. The date in this research is conversation speech which contains the maxim of quality and quantity. The results of this commercial advertisement in the form of five types of commercial advertising include Yamaha Yupiter MX version of